Does External Debt Affect Economic Growth: Evidence from South Asian Countries - Ale, Sonia Afrin; Islam, Md Shafiqul; Nessa, Hazera-Tun (International Journal of Economics and Financial Issues, 2023)
Time series econometric methods are frequently used in studies examining how external debt affects economic growth. For the period of 1980-2020, this study creates a panel dataset of five South Asian nations and examines the link between external debt and economic growth. The findings of Cross-sectionally Augmented Panel Unit Root Test by Pesaran's (2007) confirms that all variables are integrated in order I (1). To understand the error correction mechanism that determines the short-run dynamic nature of external debt and economic growth, the study uses the Cross-Sectional Dependence Autoregressive Distributed Lag (CS-ARDL) technique. A significant negative association between external debt and economic growth is found to exist in South Asia both in the long run and in the short run. Since rising foreign debt is associated with slower economic growth, the study recommends that South Asian nations should promote domestic savings and investment to lessen their reliance on external debt.